Evasive Lying in Strategic Communication - Kiryl Khalmetski; Bettina Rockenbach; Peter Werner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In a sender-receiver game we investigate if sanctions for lying induce more truth-telling. Senders may not only choose between truth-telling and (explicit) lying, but may also engage in evasive lying by credibly pretending not to know. Sanctions promote truth-telling if senders cannot engage in evasive lying. If evasive lying is possible, explicit lying is largely substituted by evasive lying, in line with the notion that evasive lying is perceived as sufficiently less psychologically costly.
Keywords: C91; D82; D83; 330